β-Fructofuranosidase production by repeated batch fermentation with immobilized Aspergillus japonicus - Mussatto, Solange I. (2009)
The fungus Aspergillus japonicus ATCC 20236 was immobilized in vegetal fiber and used in repeated batch fermentations of sucrose (200 g/l) for the production of β-fructofuranosidases (FFase). The assays were performed during eight consecutive cycles that were completed in a total period of 216 h. After each 24-h cycle of fermentation (except for the first cycle, which lasted 48 h), the fermented broth was replaced by fresh medium, and the FFase activity was determined in the replaced medium. The average value of FFase activity was a constant 40.6 U/ml at the end of the initial seven cycles, but had decreased by 22% at the end of the eighth cycle. Concurrent with these high and constant FFase values, the hydrolyzing activity of this enzyme increased during the cycles, while the transfructosylating activity decreased. As a consequence, the maximum production of fructooligosaccharides of 134.60 g/l observed in the initial 30 h of fermentation (first cycle) had gradually decreased by the end of the subsequent cycles, reaching approximately 23% of this value during cycles 4–8. Based on these results, we conclude that the present immobilization system has a great potential for application in a semi-continuous process for the production of FFase, but further studies are necessary to maintain the FFase transfructosylation activity at high levels during the overall process.